ANALYSIS OF THE INFLUENCE OF COMMUNITY PARTICIPATION ON CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAMS IN BALI PROVINCE - I Nyoman Wahyu Widiana (WORLDVIEW ( Development economic and sharia studies journal ), 2022)
The number of companies in Bali is around 358 companies, both large and medium, but the majority can be said to have implemented CSR programs, so on, but there are still some who do not implement CSR at all on the pretext that all activities are determined by the center. There are still companies that have not implemented CSR because there is still a lack of community participation in implementing CSR in Bali. This research was conducted in Bali Province, targeting the Balinese people. The population in the research is all Balinese people. The sample in this research was 65 Balinese people. This research uses multiple linear regression analysis methods to determine the factors that influence community participation in implementing the Corporate Social Responsibility (CSR) program in Bali. The results of this research are that the training variable shows that internal factors have a significant positive effect on the Implementation of the Corporate Social Responsibility (CSR) Program in Bali. External factors have a significant positive effect on the implementation of the Corporate Social Responsibility program in Bali. significant positive influence between Internal and External Factors and Corporate Social Responsibility in Bali.